Strengthening PROPER Implementation To Improve Transparency In Managing Carbon Emission Among Indonesian Manufacturing Companies - Yanto, Heri; Hasan, Ismail; Fam, Soo Fen; Raeni, Raeni (Society For Alliance, Fidelity & Advancement (SAFA), 2017)
Corporate Performance Evaluation Program (PROPER) has some objectives such as curbing carbon emissions. This program evaluates and assigns ratings to the companies' performance in managing environment. This study aims to (1) examine the effects of environmental performance (PROPER rating) on Carbon Emissions Disclosure (CED); and (2) identify the determinants of PROPER rating. Reckoning with carbon emissions checklist from Carbon Disclosure Project (CDP), data are gathered from 144 firms. The average of CED among Indonesian manufacturing companies is still relatively low (24%). Path analysis shows that CED is influenced by PROPER rating and Board Size, but not by Leverage and Profitability. Board Size and Profitability are important determinants of PROPER rating, but Leverage and Company Size are not. PROPER is considered effective to improve companies’ transparency in managing carbon emissions among Indonesian manufacturing companies.